A trapped ultracold atom force sensor with a μm-scale spatial resolution. (9th August 2018) - Alauze, X; Bonnin, A; Solaro, C; Santos, F Pereira Dos
Abstract: We report on the use of an ultracold ensemble of 87 Rb atoms trapped in a vertical lattice as a source for a quantum force sensor based on a Ramsey–Raman type interferometer. We reach spatial resolution in the low micrometer range in the vertical direction thanks to evaporative cooling down to ultracold temperatures in a crossed optical dipole trap. In this configuration, the coherence time of the atomic ensemble is degraded by inhomogeneous dephasing arising from atomic interactions. By weakening the confinement in the transverse direction only, we dilute the cloud and drastically reduce the strength of these interactions, without affecting the vertical resolution. This allows us to maintain an excellent relative sensitivity on the Bloch frequency, which is related to the local gravitational force, of 5 × 10 −6 at 1 s which integrates down to 8 × 10 −8 after one hour averaging time.